Strategi Public Relation Dalam Meningkatkan Citra Perusahaan Di Era New Normal Studi Kasus Suvana Jakarta Golf - Erlangga, Christopher Yudha (LPPM Universitas Bina Sarana Informatika, 2020)
This research is a research on how to use SWOT analysis in the Public Relations strategy of an organization. The formulation of the problem in this research is